Knowledge and performance of teachers regarding coronary artery disease prevention and its related factors - Imanipour, M; Haghani, H (Advances in Nursing & Midwifery, 2008)
Introduction Coronary artery disease (CAD) is one of the most common causes of death and of the most significant health problems in the world. Understanding and modifying its risk factors can decrease complications and mortality rate of it. Planning in this regard requires information about present knowledge and performance of people. The Purpose of this cross-sectional study was to assess knowledge and performance of teachers regarding coronary artery disease prevention and some of its related factors. Materials and Methods 590 teachers in 5 educational zones of Tehran were selected by multistage sampling method. Data were collected by a self-completed questionnaire in 2 parts: knowledge about precipitating factors and preventive performance in 3 domains including nutrition, exercise and smoking and some of effective factors. Content and test-retest methods were applied to validate and made the questionnaire reliable (r=0.9) respectively. Results Most subjects were women (68.3%) and married (89.5%) with mean age 40.36. Findings showed that the majority of subjects (63.2%) had satisfactory knowledge regarding CAD (mean=14.93±2.60). 74.5% had moderate performance in nutrition domain while 63.4% had a weak performance in exercise. 78% had a satisfactory performance in smoking domain. A significant relationship was found between educational level and knowledge as well as gender and preventive performance respectively. Conclusion Findings showed that in spite of satisfactory knowledge of teachers regarding CAD risk factors, their preventive performance in some domains was not desirable. Thus, providing appropriate and efficient educational programs to improve nutrition and exercise is necessary in this influential population with a special focus on those with lower knowledge and performance levels. Keywords: Knowledge, Performance, Coronary artery diseases, Risk factors, Prevention.